Secretive Mausoleum of Timurids - Khusenova Mekhrangiz Gayratovna (Indonesian Journal of Cultural and Community Development, 2020)
One of the brightest examples of Timurid’s architecture is the Ashatkhana monument attracting many people. Ashratkhana is also appreciated and considered heritage of not only for Uzbekistan, but also for humanity. For this reason, the mausoleum is included in The World Heritage List of UNESCO. However, some unproved and misleading information which is spread by unknown sourses made the monument have misleading opinions. It can be as a result of lack of fundamental and reliable information about the history of building, construction, describtion of the monument. This article describes the history of its construction, structure, research and its aspects as a tourist destination. This monument has been renovated many times over the years and the process is continuing